Nosocomial hepatitis C virus transmission from tampering with injectable anesthetic opioids. Issue 1 (22nd April 2015) - Hatia, Rikita I.; Dimitrova, Zoya; Skums, Pavel; Teo, Elrond Yi‐Lang; Teo, Chong‐Gee
<x xml:space="preserve">Abstract</x> The extent of provider‐to‐patient hepatitis C virus (HCV) transmission from diversion, self‐injection, and substitution ("tampering") of anesthetic opioids is unknown. To quantify the contribution of opioid tampering to nosocomial HCV outbreaks, data from health care–related HCV outbreaks occurring in developed countries from 1990 to 2012 were collated, grouped, and compared. Tampering was associated with 17% (8 of 46) of outbreaks, but 53% (438 of 833) of cases. Of the tampering outbreaks, six (75%) involved fentanyl, five (63%) occurred in the United States, and one each in Australia, Israel, and Spain. Case counts ranged from 5 to 275 in the tampering outbreaks (mean, 54.8; median, 25), and 1‐99 in the nontampering outbreaks (mean, 10.4; median, 5); between them, the difference in mean ranks of counts was significant (P < 0.01). To estimate HCV transmission risks from tampering, risk‐assessment models were constructed, and these risks compared with those from surgery. HCV transmission risk from exposure to an opioid preparation tampered by a provider of unknown HCV infection status who is a person who injects drugs (PWID; 0.62%; standard error [SE] = 0.38%) exceeds 16, 757 times the risk from surgery by a surgeon of unknown HCV infection status (0.000037%; SE = 0.000029%) and 135 times by an HCV‐infected surgeon (0.0046%; SE = 0.0033%). To pose a 50% patient transmission risk, an infected surgeon may take 30 years, compared to <1 year for a PWID tamperer, and weeks or days for a PWID tamperer who intensifies access to opioids. Conclusion: Disproportionately, many cases of HCV infection from nosocomial outbreaks were attributable to provider tampering of anesthetic opioids. Transmission risk from tampering is substantially higher than from surgery. (Hepatology 2015;62:101‐110)